Guidelines on multidisciplinary approaches for the prevention and management of diabetic foot disease (2020 edition). Issue 1 (6th July 2020) - Wang, Aiping; Lv, Guozhong; Cheng, Xingbo; Ma, Xianghua; Wang, Wei; Gui, Jianchao; Hu, Ji; Lu, Meng; Chu, Guoping; Chen, Jin'an; Zhang, Hao; Jiang, Yiqiu; et al.
Abstract: In recent years, as living standards have continued to improve, the number of diabetes patients in China, along with the incidence of complications associated with the disease, has been increasing. Among these complications, diabetic foot disease is one of the main causes of disability and death in diabetic patients. Due to the differences in economy, culture, religion and level of medical care available across different regions, preventive and treatment methods and curative results for diabetic foot vary greatly. In multidisciplinary models built around diabetic foot, the timely assessment and diagnosis of wounds and appropriate methods of prevention and treatment with internal and external surgery are key to clinical practice for this pathology. In 2019, under the leadership of the Jiangsu Medical Association and Chinese Diabetes Society, the writing group for the Guidelines on multidisciplinary approaches for the prevention and management of diabetic foot disease (2020 edition) was established with the participation of scholars from the specialist areas of endocrinology, burn injury, vascular surgery, orthopedics, foot and ankle surgery and cardiology. Drawing lessons from diabetic foot guidelines from other countries, this guide analyses clinical practices for diabetic foot, queries the theoretical basis and grades and gives recommendations based on the characteristics of the pathology in China. This paper begins with assessments and diagnoses of diabetic foot, then describes treatments for diabetic foot in detail, and ends with protections for high-risk feet and the prevention of ulcers. This manuscript covers the disciplines of internal medicine, surgical, nursing and rehabilitation and describes a total of 50 recommendations that we hope will provide procedures and protocols for clinicians dealing with diabetic foot. Registry number: IPGRP-2020cn124